Requirements for compatibility between international accounting standards and the Libyan tax system to reduce tax evasion (Economic studies journal, 2021)
AbstractThe study dealt with the requirements of compatibility between international accounting standards and the Libyan tax system to reduce tax evasion. The study aimed to define the requirements for compatibility between international accounting standards and the tax system, as well as enriching Libyan libraries because there is a severe lack of studies related to the subject of the study, where 78 questionnaires were distributed, of which 73 are valid for statistical analysis. The study used the inductive method to list previous studies, and the statistical program Spss was used to analyze the data.The study reached several results, the most prominent of which is that there are requirements for compatibility between international accounting standards and the Libyan tax system to reduce tax evasion, including the issuance of international accounting standards as well as the tax law at the same time and an attempt to unify the objectives between international accounting standards and the tax system, as well as assessing the tax system periodically to determine On the extent to which he took what was stated in the international accounting standards and that the application of some international accounting standards requires an amendment to the laws in Libya or the regulations, legislation, instructions and communications issued in accordance with them, as well as the request of the concerned authorities (the Ministry of Finance) scientific qualification and practical training for those primarily concerned with the application of the tax system in order to ensure The correct application of the accounting system that is compatible with international standards and the issuance of professional and official regulations and laws that impose the application of international accounting standards.The study recommended the need for the Libyan legislator to issue the tax law in line with the issuance of international accounting standards to reduce tax evasion, as well as the competent authorities to try to unify the objectives between international accounting standards and the tax system and evaluate the tax system periodically to determine the extent to which it took what was stated in the accounting standards International, as well as amending and issuing some laws in Libya in line with some international accounting standards